2021
DOI: 10.21037/apm-20-2211
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status and quality of life in patients with end-stage renal disease undergoing maintenance hemodialysis

Abstract: Background: This study aimed to identify the association of factors and poorer mental health status and examinate the correlation between mental health status and quality of life (QOL) in patients with end-stage renal disease (ESRD) undergoing maintenance hemodialysis.Methods: A total of 190 patients were included in this observational, cross-sectional study. Psychological states of ESRD patients undergoing maintenance hemodialysis were evaluated by the Chinese version symptom checklist-90 (SCL-90) and QOL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
5
0
2
Order By: Relevance
“…Some studies stated that low QoL scores significantly contribute to developing depressive symptoms, and those with no depression, anxiety, and stress had better QoL. 29 , 31 , 39 , 51–53 This supports our findings of a negative correlation between QoL domains and GAD7 and PHQ9 scores, with lower depression and GAD scores correlating with higher QoL domains. Thus, screening CKD patients and hemodialysis patients for depression and anxiety are of paramount importance.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies stated that low QoL scores significantly contribute to developing depressive symptoms, and those with no depression, anxiety, and stress had better QoL. 29 , 31 , 39 , 51–53 This supports our findings of a negative correlation between QoL domains and GAD7 and PHQ9 scores, with lower depression and GAD scores correlating with higher QoL domains. Thus, screening CKD patients and hemodialysis patients for depression and anxiety are of paramount importance.…”
Section: Discussionsupporting
confidence: 88%
“…Low HRQOL scores in patients receiving maintenance HD have been associated with a higher risk of hospitalization and mortality [10,[53][54][55], poorer mental health [56] and nutritional status [57], fatigue [58], chronic pain [59], and depressive and anxiety symptoms [44,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that patients who have a lower educational level or no education, patients who are not married or widowed, patients who are unemployed, patients who have a low monthly income, and patients who have multiple comorbidities usually have poorer mental health, which directly affects their HRQoL and is negatively correlated with their quality of life. In addition, the quality of life of patients is negatively affected by a hemodialysis history of <2 years, lack of regular exercise, and lack of moderate-intensity exercise [ 29 , 43 , 44 ]. Therefore, regular physical activity is positively correlated with improvements in quality of life, PCS, and MCS.…”
Section: Discussionmentioning
confidence: 99%